Yield-related agronomic traits evaluation for hybrid wheat and relations of ethylene and polyamines biosynthesis to filling at the mid-grain filling stage - Wei-bing YANG; Zhi-lie QIN; Hui SUN; Xiang-zheng LIAO; Jian-gang GAO; Yong-bo WANG; Qiling HOU; Xian-chao CHEN; Li-ping TIAN; li-ping ZHANG; Jin-xiu MA; Zhao-bo CHEN; et al. (Journal of Integrative Agriculture, 2020)
Because of the yield increase of 3.5–15% compared to conventional wheat, hybrid wheat is considered to be one of the main ways to greatly improve the wheat yield in the future. In this study, we performed a principal component analysis (PCA) on two-line hybrids wheat and their parents using the grain weight (GW), the length of spike (LS), the kernel number of spike (KSN), and spike number (SPN) as variables. The results showed that the variables could be classified into three main factors, the weight factor (factor 1), the quantity factor 1 (factor 2) and the quantity factor 2 (factor 3), which accounted for 37.1, 22.6 and 18.5%, respectively of the total variance in different agronomic variables, suggesting that the GW is an important indicator for evaluating hybrid combinations, and the grain weight of restorer line (RGW) could be used as a reference for parents selection. The hybrid combination with a higher score in factor 1 direction and larger mid-parent heterosis (MPH) of the GW and its parents were used to carry out the analysis of grain filling, 1-aminocylopropane-1-carboxylicacid (ACC) and polyamine synthesis related genes. The results suggested that the GW of superior grain was significantly higher than that of inferior grains in BS1453×JS1 (H) and its parents. Both grain types showed a weight of H between BS1453 (M) and JS1(R), and a larger MPH, which may be caused by their differences in the active filling stage and the grain filling rate. The ADP-glucose pyrophosphorylase (AGPase), granule bound starch synthase I (GBSSI), starch synthase III (SSS), and starch branching enzyme-I (SBE-I) expression levels of H were intermediated between M and R, which might be closely related to MPH formation of the GW. Compared with R and H, the GW of M at maturity was the lowest. The expression levels of spermidine synthase 2 (Spd2), ornithine decarboxylase (ODC) and S-adenosylmethionine decarboxylase (SAMDC) had significantly positive correlations with the grain filling rate (r=0.77*, 0.51*, 0.59*), suggesting their major roles in the grain filling and heterosis formation. These provide a theoretical basis for improving the GW of photo-thermo-sensitive male sterile lines (PTSMSL) by changing the endogenous polyamine synthesis in commercial applications.